Robot Auditory Interface Design Factor Attributes and the Level Values Based on UX using TTS System - Eun Chung, Seung; Young Ryoo, Han (International Journal of Engineering and Technology, 2019)
The purpose of this study is to suggest the attributes of the design factors and the level values for each attribute for the service robot’s auditory interface design. To do so, the main design factors of the auditory interface were organized through the research on the existing literature, and then the attributes and the level values of the auditory interface design factors that can be designed using the SSML from the TTS system were organized. A survey was conducted to verify whether the organized values have a significance meaning in the aspect of the user experience, and the level values which had differences in all the functional/service experience, the interaction experience, and the emotional experience have been organized. From the results, ‘Prototype of the sound effect’, ‘Gender’, ‘Pitch’, ‘Pitch range’, and ‘Rate’ were verified to be useable as the attributes of the auditory interface design factors to measure the overall user experience with the robots. Two out of the 15 investigated subordinate level values had been deleted and integrated so that a total of 13 level values have been suggested in the end. This research has a significant meaning in a way that it offers suggestions to the designers of the robots that provide auditory interface through the TTS system the usable design factors for the user experience-centered designs.